TELAAH KRITIS IMPLIKASI PEMBANGUNAN TERHADAP KEMISKINAN DI INDONESIA - Pramestisari, Nyoman Ayu Sukma (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
The complexity of the problems of poverty and social inequality in Indonesia becomes a paradox when the development that has been promoted for almost 50 years has not brought significant changes in alleviating poverty. The still high percentage of poor people in Indonesia means that welfare cannot be reached by all Indonesian people. Considering that the indicators of poverty and welfare are economic, it cannot be separated from the enactment of the current global system of neo-liberalism. This paper tries to dissect the failure of development practices in Indonesia, which in its implementation is very contrary to the principle of prioritizing the interests of the people as a result of being infected with the logic of neo-liberalism. This condition actually ends up widening social inequalities as well as perpetuating poverty. The indications are getting stronger when the government and public space seem to have become "traders" and objectify society in development cases for their interests. By using Habermas' communicative action approach and deliberative space, he feels he is capable of being a solution to this problem in order to achieve the re-actualization of Indonesia's development independently and based on solidarity in the interests of the nation.